2013
DOI: 10.1111/echo.12172
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Observer Reproducibility of Speckle Tracking Echocardiography in Congenital Heart Disease Patients

Abstract: Speckle tracking echocardiography is feasible in 80% of adult patients with congenital heart disease and shows excellent intra- and inter-observer reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Increasing data suggest that longitudinal strain is a strong predictor of adverse outcome in patients with different cardiovascular diseases . Our study clearly showed that assessment of myocardial function using deformation imaging was easy, feasible, and highly reproducible.…”
Section: Discussionsupporting
confidence: 61%
“…Increasing data suggest that longitudinal strain is a strong predictor of adverse outcome in patients with different cardiovascular diseases . Our study clearly showed that assessment of myocardial function using deformation imaging was easy, feasible, and highly reproducible.…”
Section: Discussionsupporting
confidence: 61%
“…Speckle-tracking echocardiography (STE) is a non-invasive modality for the assessment of myocardial deformation. Reference ranges have been published for the pediatric population [14,15], and STE has increasingly been applied in patients with congenital heart disease [16][17][18]. STE has several characteristics that make it appealing for evaluation of ventricular function in this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…However, much data showed the feasibility and reproducibility of this technique, which is reported to be good in different studies including patients with different CHDs ( 119 , 120 ) and modest in patients with complex anatomy such as single ventricle physiologies ( 121 , 122 ).…”
Section: Systemic Rv In Biventricular Physiologymentioning
confidence: 99%
“…However, much data showed the feasibility and reproducibility of this technique, which is reported to be good in different studies including patients with different CHDs (119,120) and modest in patients with complex anatomy such as single ventricle physiologies (121, 122). To enhance the reliability and reproducibility of strain analysis, a standardized approach is fundamental, and this follows the EACVI consensus document recommendations for adult patients (123).…”
Section: State-of-the-art and Future Perspective Of Ste To Assess Car...mentioning
confidence: 99%